Is The Sociopath Socially Intelligent? A New Framework For Understanding Sociopathy - ALSAWALQA, R. O (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The characteristics of sociopathy vary in the context of its overlap with the concept of "psychopathy, and anti-social personality". The characteristic of social intelligence is associated with who is infected with sociopathy. Therefore, this article was designed to follow the scientific heritage of sociopathy, to specify its characteristics, and to analyze them in order to clarify the possibility of describing the sociopath as being intelligent socially. In light of the analysis of the concept of social intelligence, it is not possible to describe the sociopath as being intelligent socially, even if he has apparent superficial charm. RESUMEN Las características de la sociopatía varían en el contexto de su superposición con el concepto de "psicopatía y personalidad antisocial". La característica de la inteligencia social está asociada con quién está indentificado con sociopatía. Por lo tanto, este artículo fue diseñado para seguir el patrimonio científico de la sociopatía, para especificar sus características y analizarlas con el fin de aclarar la posibilidad de describir al sociópata como inteligente socialmente. A la luz del análisis del concepto de inteligencia social, no es posible describir al sociópata como inteligente socialmente, incluso si tiene un aparente encanto superficial.